LEGAL REVIEW ON E-COMMERCE AND THE BLUEPRINT OF THE ASEAN ECONOMIC COMMUNITY - Ikbal, Mohammad (Tadulako University, 2017)
Revolution and development of Information and Transactions Elektrnik indirectly helped change the way of trading or buying and selling activities, using the virtual world (online) or better known as electronic transactions (e-commerce). In the framework of ASEAN Trade Integration and Liberalization it has been agreed that the Blueprint ASEAN Economic Community (AEC) with one of its pillars is ASEAN as a region with high economic competitiveness, with elements of competition rules, consumer protection, intellectual property rights, infrastructure development, taxation and E-commerce. Blueprint is a guide for ASEAN member countries to achieve a strategic timetable and timing of achievement of each pillar that has been agreed.